2017
DOI: 10.1038/ncomms15890
|View full text |Cite
|
Sign up to set email alerts
|

HTLV-1-induced leukotriene B4 secretion by T cells promotes T cell recruitment and virus propagation

Abstract: The human T-lymphotropic virus type 1 (HTLV-1) is efficiently transmitted through cellular contacts. While the molecular mechanisms of viral cell-to-cell propagation have been extensively studied in vitro, those facilitating the encounter between infected and target cells remain unknown. In this study, we demonstrate that HTLV-1-infected CD4 T cells secrete a potent chemoattractant, leukotriene B4 (LTB4). LTB4 secretion is dependent on Tax-induced transactivation of the pla2g4c gene, which encodes the cytosoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…Several human viruses and among them lymphotropic viruses have been extensively used in these models [ 22 , 23 , 30 ]. Thus, hu-mice have been used to approach the pathogenic activity of HTLV-1 Tax in a more biological model than cultured cells [ 25 27 , 31 ]. Here we have investigated the role played by the Tax PBM in the lymphoproliferation triggered by HTLV-1 infection of hu-mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several human viruses and among them lymphotropic viruses have been extensively used in these models [ 22 , 23 , 30 ]. Thus, hu-mice have been used to approach the pathogenic activity of HTLV-1 Tax in a more biological model than cultured cells [ 25 27 , 31 ]. Here we have investigated the role played by the Tax PBM in the lymphoproliferation triggered by HTLV-1 infection of hu-mice.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 , 11 In this study, we explored the benefit of an optimized high-throughput sequencing (HTS) clonality method as a quantitative molecular approach to monitor the malignant clone identified at diagnosis and better evaluate therapeutic response. 10 , 12 The method enables the genome-wide mapping of HTLV-1 integration sites and the simultaneous quantification of the abundance of the corresponding clones. It includes several critical modifications that overcome the limitations of previously reported protocols, 13 , 14 increasing sensitivity, facilitating multiplexing, and significantly reducing both the cost and hands-on time ( Supplementary Methods ).…”
mentioning
confidence: 99%
“…Therefore, the consistent CCR4 expression on ATL cells and HTLV-1 transformed T cells may be attributable to the perception that HTLV-1 preferentially infects CCR4 + T cells through the recruitment of CCR4 + T cells via CCL22 and/or due to some growth advantages of HTLV-1-infected CCR4 + T cells in vivo as well as in vitro (Yoshie et al, 2002). However, Sugata et al (2016) showed that HBZ upregulates CCR4 expression in ATL and HTLV-1 infected cells and thus, migration and proliferation of those cells are increased, thus CCR4 may not be initially expressed on the infected cells (Percher et al, 2017). CD4 + FOXP3 + cells are observed at a high frequency in ATL patients (Toulza et al, 2009).…”
Section: Ccl17/tarc Ccl22/mdc and Ccr4mentioning
confidence: 99%